Implementation of The Strategic Role of The Government Internal Supervision Personnel (APIP) In Improving the Quality of Supervision (Study at the Inspectorate of Bandar Lampung City) - Septi Dwi Kurnia (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purposes of this research were 1) to analyze the Government Internal Supervision Personnel (Bahasa: Aparat Pengawasan Intern Pemerintah (APIP)) strategy in improving the quality of supervision, 2) to find the goal of an effective and efficient result. The benefits of this study theoretically were benefits and practical benefits. As for the theoretical benefits, it was hoped that this research will give birth to scientific concepts to be used as material for a deeper study of APIP in improving the quality of supervision. Meanwhile, the practical benefits were a). as a guideline and input for APIP and government internal supervisory institutions in an effort to improve the quality of supervision, b). as a study material for academics to add insight, c). related to the role of APIP in preventing abuse of State Civil Apparatus (Bahasa: Aparatur Sipil Negara (ASN)) authority. This study used descriptive research with a qualitative approach. Through this approach, this study was able to provide a thorough and in-depth understanding of the performance of the Inspectorate of Bandar Lampung City in an effort to improve the quality of supervision.Keywords: implementation, strategic role, APIP, inspectorate